1997
DOI: 10.1002/hep.510250335
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and risk factors of community-acquired hepatitis C in a cohort of Italian blood donors

Abstract: We performed a prospective study in a cohort of repeat To assess the incidence and source of community-acblood donors to estimate the risk of acquiring HCV infection quired hepatitis C virus (HCV) infection among subjects among individuals without parenteral exposure, and to invesat low risk for blood-borne diseases, we prospectively tigate the possible cause of infection. studied a cohort of 16,515 repeat blood donors over a mean follow-up time of 36 months. Second-and third-PATIENTS AND METHODS generation me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
2
4

Year Published

1997
1997
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 5 publications
(6 reference statements)
2
30
2
4
Order By: Relevance
“…Conversely, the incidence of community-acquired HCV infection calculated in the same area in the 1990s was 1 per 10 000 person-years. 14 Even if we hypothesize a 10 times higher incidence of nontransfusional sources in the preceding decades, the cumulative frequency after a mean follow-up of 18.4 years would be 1 per 54.3. This would lead to no more than 5 cases (1.84%) being inappropriately classified as "posttransfusional.…”
Section: Discussionmentioning
confidence: 94%
“…Conversely, the incidence of community-acquired HCV infection calculated in the same area in the 1990s was 1 per 10 000 person-years. 14 Even if we hypothesize a 10 times higher incidence of nontransfusional sources in the preceding decades, the cumulative frequency after a mean follow-up of 18.4 years would be 1 per 54.3. This would lead to no more than 5 cases (1.84%) being inappropriately classified as "posttransfusional.…”
Section: Discussionmentioning
confidence: 94%
“…25,26,79 Nevertheless, some of these studies also noted that patients with genotype 1b were data need to be confirmed.…”
Section: Anti-hcv-positive (Eia-2) Patients Presenting With Chronicmentioning
confidence: 99%
“…In view of the possibility RIBA positive to 2% to 40% for those who are RIBA indeterof a false-negative EIA-2 result, modified diagnostic algominate, to none among those who are RIBA negative, giving rithms are recommended for immunocompromised patients an overall detection rate of 35% to 45% (Table 1). [24][25][26][27][28][29][30][31][32][33] Thus, and patients with acute hepatitis C.…”
mentioning
confidence: 99%
“…On a worldwide level, many cases are related to medical procedures, including blood transfusions, contaminated vaccination needles, and hemodialysis. [9][10][11] In Egypt, which has among the highest reported prevalence of HCV (15%), transmission is thought to have occurred with needle reuse during a national program of schistosomiasis vaccination. 12 Transmission has also been linked to folk remedies and other community-based needle practices, including acupuncture.…”
Section: Transmission and Risk Factorsmentioning
confidence: 99%